Penentuan Harga Pokok Beras di Kelurahan Imandi Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Kolamban, Angreyani Prisilia; Katiandagho, Theodora Maulina; Benu, Noortje Marsellanie (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to calculate the cost of production of rice in Imandi Village and compare the cost of rice with market prices and prices set by the government. This research uses a quantitative descriptive approach method, data collection is primary and secondary by conducting interviews with rice farmers. This study shows that the results of the calculation of the cost of goods sold, the total cost of the total respondents is Rp270,095,155. and the amount of rice production produced is 39,452 kg so that the cost of goods sold of rice in Imandi Village is Rp6,846/kg.